How does working capital management affect the profitability of Vietnamese small- and medium-sized enterprises?. Issue 1 (20th February 2017) - Tran, Hien; Abbott, Malcolm; Jin Yap, Chee
Abstract : Purpose: Well-designed and implemented working capital management (WCM) will encourage positive returns for a business and establish the firm's value, while ineffective management will undoubtedly lead to failure of the enterprise. The paper aims to discuss these issues. Design/methodology/approach: In business, fixed capital and working capital are the two main forms of capital used. The current assets used in the business as working capital for day-to-day operations include raw materials, work in progress, finished goods, bills receivable, cash and bank balance. This paper analyses the relationship between WCM and profitability in Vietnamese small- and medium-sized enterprises (SMEs) after integration into the global economy. Findings: The results suggest that SME owner-managers can increase their firm's profitability by reducing the number of days of accounts receivable, accounts inventories and accounts payable to an optimal minimum. In addition, a robustness check of this study indicates that high profitability will be achieved, with an optimal level of working capital investment in accounts inventories, accounts receivable and accounts payable. Originality/value: No work of this sort has been applied to Vietnamese circumstances. It is also rare in SE Asia more generally.